Physical and Organoleptic Characteristics of Meatballs Made from a Combination of Rabbit Meat and Chicken Meat - Wardi Wardi; Oscar Aditya Novanda; Andri Haryono Awalokta Akusuma; Puji Astuti; Agung Mugi Widodo; Putri Awaliya Dughita; Bagus Andika Fitroh (Journal of Tropical Animal Science and Technology, 2026)
P This study was conducted at the Laboratory of Universitas Islam Batik Surakarta during December to January 2024 to evaluate the physical and organoleptic characteristics of meatballs prepared from a combination of rabbit meat and chicken meat, and to analyze the effect of different proportions of the two types of meat on product quality. A completely randomized design (CRD) was applied with five treatments: P0 (100% rabbit meat), P1 (100% chicken meat), P2 (50% chicken meat + 50% rabbit meat), P3 (75% chicken meat + 25% rabbit meat), and P4 (25% chicken meat + 75% rabbit meat). The parameters observed included elasticity, aroma, color, and overall preference. The results indicated that differences among treatments were not statistically significant for all parameters. However, treatment P4 to be more preferred compared to P0. The combination of chicken and rabbit meat influenced elasticity but did not produce any negative effects on the organoleptic quality of the meatballs.